The Effect of Service Quality and Maternal Satisfaction of Children Under Five on the Behavior of Mothers Visiting “Posyandu” - Agung Suharto; Budi Joko Santosa; K Kasiati (Health Notions, 2021)
Background: “Posyandu” is a means for the community to obtain basic health services which includes five main “posyandu” activities, including: maternal and child health, family planning, nutrition, immunization and overcoming diarrhea. In terms of quantity, the development of the number of posyandu is very encouraging, because the ratio of posyandu to village is 3.51 “posyandu”. This study aims to determine the effect of service quality and maternal satisfaction of children under five on the behavior of mothers visiting “posyandu”. Methods: The design of this research was cross sectional. Population was 100 and sample was 80 people. Independent variable were the quality of service and satisfaction and dependent variable was the behavior (frequency) of visiting the “posyandu”. Data analysis was done by: descriptive analysis, and logistic regression. Results: The most of respondents said the quality of service was good as many as 56.3% and a small proportion of respondents said the quality of service was sufficient as much as 8.8%. Most of the respondents said that the level of satisfaction was satisfied as much as 55% and a small proportion of respondents said the level of satisfaction was satisfied as much as 6.3%. Most of the h good behavior was 71.3% and a small proportion of: less than 2.5%. Obtained a significant effect of service quality on the behavior of mothers under five visiting “posyandu” (p-value = 0.005) and there was a significant effect of satisfaction with the behavior of mothers under five visiting “posyandu” (p-value = 0.011). Conclusion: the quality of service and satisfaction of mothers under five have an effect on the behavior of mothers visiting “posyandu”. Keywords: quality; satisfaction; behavior; “posyandu”